Ametropías y su incidencia en el rendimiento escolar en los estudiantes del colegio EIWA de la ciudad de Milagro, periodo abril-febrero 2025 - Armijo Tierra, Pamela Nicole (2025)
Through this research topic we will analyze the effect of ametropia and its relationship with school performance in the EIWA Educational Unit of the city of Milagro. The most common ametropias such as myopia, stigmatism, and hyperopia are the cause of learning problems, affecting the academic performance of students. (Vera Alava, 2023). A non-experimental, cross-sectional descriptive methodology was applied, the techniques used were surveys, optometric tests and interviews with those involved. The statistical software IBM SPSS version 27 was used for the respective tabulation of the data. Among the findings, 29.5% of the students reported a previous diagnosis of ametropia, with myopia being the most frequent (18.3%). Furthermore, excessive use of electronic devices exacerbates visual problems, while symptoms such as difficulty reading, eye fatigue, and headaches affect concentration and academic performance (León Vázquez et al., 2022). The importance of implementing prevention and detection programs for visual problems is highlighted to support the learning process and improve the quality of life of students.